Politics in emotion the song of Telangana - Muppidi, Himadeep (Routledge, Taylor & Francis Group, 2015)
The work focuses on a subaltern local sovereignty movement called "Telangana" in India. Over the last ten years, this movement has engaged in a massive political mobilization, including strikes, rallies, work stoppages, occupation of public spaces, electoral contests, 200 and more political suicides and media battles.